Adsorption of Cr(VI) Ions on Magnetite Nano-Particles (Fe3O4): Kinetic and thermodynamic studies - Çiftçi, Hakan; Ersoy, Bahri (El-Cezerî Journal of Science and Engineering)
This article intends to investigate the kinetic and thermodynamic properties of adsorption process of hexavalent chromium [Cr(VI)] ions on magnetite nano-particles (Fe 3 O , MNPs). In accordance with this purpose, MNPs were synthesized by chemical co-precipitation method and characterized by FTIR, TEM and VSM methods at first. After that, a series of adsorption experiments were performed for removal of Cr(VI) ions from aqueous media by MNPs. Finally, thermodynamic and kinetic properties of Cr(VI) adsorption on MNPs were investigated. Mean particle size and magnetization saturation (Ms) of synthesized MNPs were about 15 nm and be 75 emug -1 4 , respectively. Under optimum adsorption conditions, adsorption capacity and Cr(VI) removal percentage were found to be 33.45 mg/g and 88%, respectively. According to calculated thermodynamic parameters after adsorption experiments, Cr(VI) adsorption process was a result of endothermic reactions. Langmuir and Freundlich isotherm models were investigated and it was observed that the removal of Cr(VI) could be better described by the Langmuir model. Kinetic investigations showed that the pseudo-second-order model have a better description of the Cr(VI) adsorption.

Bu çalışmada, hekzavalent krom [Cr(VI)] iyonlarının manyetit nano-partikülleri (Fe3O4, MNP) ile adsorpsiyonu prosesinin kinetik ve termodinamik özelliklerinin araştırılması amaçlanmıştır. Bu amaç doğrultusunda, ilk olarak kimyasal ikili çöktürme tekniği kullanılarak MNP sentezlendi ve elde edilen ürünler FTIR, TEM ve VSM gibi metotlar ile karakterize edildi. Daha sonra, sulu ortamdan Cr(VI) iyonlarının giderilmesi için MNP ile bir dizi adsorpsiyon deneyleri yapıldı. Son olarak da Cr(VI) iyonlarının MNP ile adsorpsiyonu prosesinin kinetik ve termodinamik çalışmaları yapıldı. Sentezlenen nano-partiküllerin ortalama tene boyutunun 15 nm ve mıknatıslanma doygunluğunun da 75 emug-1 olduğu tespit edildi. Optimum adsorpsiyon şartlarında, adsorpsiyon kapasitesi ve Cr(VI) giderim yüzdesi sırasıyla 33.45 mg/g ve %88 olarak hesaplandı. Adsorpsiyon deneyleri sonrası hesaplanan termodinamik parametrelere göre MNP ile Cr(VI) adsorpsiyonu endotermik reaksiyonların sonucu oluşan bir proses olduğu söylenebilir. Langmuir ve Freundlich izoterm modelleri araştırıldı ve adsorpsiyon prosesinin Langmuir modeli ile daha iyi açıklanabilir olduğu tespit edildi. Kinetik araştırmalar sonucunda ise MNP ile Cr(VI) iyonlarının adsorpsiyonu için sözde-ikinci-derece kinetik model ile daha iyi bir açıklama getirilebilir
Cr(VI) İyonlarının Manyetit Nano-Partikülleri (Fe3O4) Üzerine adsorpsiyonu: Kinetik ve termodinamik Çalışmalar
Keywords: Nanomagnetite; Adsorption Kinetics; Adsorption Thermodynamics; Nanomanyetit; Cr(IV); Adsorpsiyon Kinetiği; Adsorpsiyon Termodinamiği